ANALISIS PENGARUH PELATIHAN DAN PENGEMBANGAN, KOMPENSASI SERTA KOMPETENSI TERHADAP KINERJA KARYAWAN (Studi Pada PT. Pos Semarang) - Rahinnaya, Rafdan; Perdhana, Mirwan Surya (Diponegoro Journal of Management, 2016)
This study aimed to investigate the effect of training and development , compensation and competency on the performance of employees at PT . Pos Semarang . Problems that occur in this study is the training and development is uneven , the compensation system is not suitable for the employees and the lack of competence of employees.This study uses training and development, compensastion, and competency as the independent variables and employee performance as the dependent variable. This study uses a quantitative method as the data analysis by collecting questionnaires and doing interviews. The study involved 70 manager and asistant manager as trespondentsBased on the results of quantitative research , the level of influence of training and development, compensation and competency on employee performance is moderate . While training and development has no effect on the performance of the employee but compensation and competency have an influence on employee performance.